The Legal Force Of Interfaith Marriage In Indonesia - Novea Elysa Wardhani (Al-Makki Publisher, 2023)
religions to obtain legality, but the existence of the life of a pair of people of different religions as husband and wife is a reality that cannot be denied in fact, many couples want to live together as husband and wife but are constrained to different religions or beliefs. Some choose a way of life to be together without marriage ties or